Otimização multivariada dos parâmetros cromatográficos para determinação de furfural em vinho branco por CLAE-DAD - Carletto, Joana Paula Moreira (2013)
This work describes the optimization of an analytical method for the direct determination of furfural in white wines by High Performance Liquid Chromatography with a diode array detector (HPLC-DAD). No prior treatment of samples was needed. In order to achieve the objectives of the work, a multivariate optimization process was performed, employing the Surface response Methodology based on the Doehlert matrix. Three variables were selected for optimization: the flow rate of mobile phase, the temperature of analytical column and the proportion of water, in relation to acetonitrile, in the mobile phase. Different responses were tested for the system, taking into account the sensitivity of the method, the retention time and the chromatographic resolution. In the multivariate optimized conditions, the flow rate of the mobile phase was 0.70 mL min-1, the temperature of the column was 51 oC and the proportion of water in the mobile phase was 57%. A comparative study was carried out to evaluate the performance of the system that was optimized by a multivariate approach with that optimized through an univariate approach, which employed only the sensitivity as response. The sensitivity of the method optimized by multivariate strategy was approximately 40% higher than that observed for the method optimized through univariate strategy, without significant lost of selectivity. The limit of quantification of the optimized method was 0.021 mg L-1. The method was applied in the determination of furfural in several white wines, purchased in the market of the Rio de Janeiro, Brazil. A recovery test was performed by spiking the samples with different concentrations of furfural. Recovery percentages between 80.9 and 141% were observed, indicating that the method can be applied for the determination of furfural in this kind of sample.